Synchronization of Inertial Neural Networks with Time-Varying Delays - LU Shuang;GAO Yanbo (Nantong Daxue xuebao. Ziran kexue ban)
This paper addresses the synchronization problem for inertial neural networks with time-varying delay. By using a proper variable substitution to transform the original system into a first-order differential system, constructing the Lyapunov-Krasovskii functional( LKF) containing the Kronecker product of matrices, applying Jensen inequality, the reciprocally convex inequality and the linear matrix inequality( LMI) technique to estimate the derivative of the LKF, a novel synchronization criterion in terms of LMIs is obtained, and a design method for the error feedback controller is presented based on the synchronization criterion. And a numerical simulation example shows the effectiveness of the proposed results.